Reconstruction of the Late Holocene climate and environmental history from North Bolgoda Lake, Sri Lanka, using lipid biomarkers and pollen records. (20th March 2020) - Gayantha, Kasun; Routh, Joyanto; Anupama, Krishnamurthy; Lazar, Jean; Prasad, Srinivasan; Chandrajith, Rohana; Roberts, Patrick; Gleixner, Gerd
ABSTRACT: The catastrophic impact and unpredictability of the Indian Ocean Monsoon (IOM) over South Asia are evident from devastating floods, mudslides and droughts in one of the most densely populated regions of the globe. However, our understanding as to how the IOM has varied in the past, as well as its impact on local environments, remains limited. This is particularly the case for Sri Lanka, where erosional landscapes have limited the availability of well‐stratified, high‐resolution terrestrial archives. Here, we present novel data from an undisturbed sediment core retrieved from the coastal Bolgoda Lake. This includes the presentation of a revised Late Holocene age model as well as an innovative combination of pollen, source‐specific biomarkers, and compound‐specific stable carbon isotopes of n‐ alkanes to reconstruct the shifts in precipitation, salinity and vegetation cover. Our record documents variable climate between 3000 years and the present, with arid conditions c. 2334 and 2067 cal a bp. This extreme dry period was preceded and followed by more wet conditions. The high‐resolution palaeoenvironmental reconstruction fills a major gap in our knowledge on the ramifications of IOM shifts across South Asia and provides insights during a time of major redistribution of dense human settlements across Sri Lanka.